(untitled) (Karapan Network Journal : Journal Computer Technology and Mobile Ad Hoc Network, 2025)
Computer networks are the main infrastructure in modern office environments that support various digital services. In general, wired networks are known for their stability and high performance, while wireless networks offer flexibility and mobility. However, the differences in the technical characteristics of these two types of networks cause variations in performance that need to be studied empirically in real office conditions. This study aims to analyze and compare the performance of wired and wireless networks in an office environment based on Quality of Service (QoS) parameters. This study uses a quantitative method with an experimental approach. Testing was conducted on two network scenarios, namely wired and wireless networks, with measurement parameters including throughput, delay, jitter, and packet loss. Data collection was carried out through several tests with the same data traffic scenario, then analyzed using descriptive statistics. The results showed that wired networks had superior performance compared to wireless networks in all QoS parameters. Wired networks produced an average throughput of 370 Mbps, a delay of 5.8 ms, jitter of 4.9 ms, and packet loss of 0.8%. Meanwhile, wireless networks produced an average throughput of 210 Mbps, a delay of 13.5 ms, jitter of 9.4 ms, and packet loss of 2.1%. These differences are influenced by the transmission medium, network access mechanism, and environmental conditions. This study concludes that wired networks are more reliable for supporting office applications that require stability and high performance, while wireless networks remain relevant for supporting user mobility. Further research is recommended to examine the impact of the latest Wi-Fi standards and more complex network load scenarios.